Effect of triamterene on leucocyte sodium and potassium levels in heart disease. Issue 6020 (22nd May 1976) - Donaldson, E K; Patrick, J; Sivapragasm, S; Ming, M O; Alleyne, G A
Abstract : Sodium and potassium levels in plasma and leucocytes and the sodium efflux rate constants of leucocytes were measured in patients with congenital heart disease not on treatment, patients with valvular heart disease being treated with digoxin and conventional diuretics, and patients with valvular heart disease receiving digoxin and either conventional diuretics or triamterene or both. The group being treated with digoxin and conventional diuretics showed low cellular potassium levels, low sodium efflux rate constants, and a rise in cellular sodium levels. Patients given triamterene showed a rise in potassium levels in plasma and cells and in the sodium efflux rate constant.